Integrated process of two stage cultivation of Nannochloropsis sp. for nutraceutically valuable eicosapentaenoic acid along with biodiesel. (October 2015) - Mitra, Madhusree; Patidar, Shailesh Kumar; Mishra, Sandhya
Graphical abstract: Highlights: Marine alga Nannochloropsis sp. was studied for EPA production. % EPA was increased by two phase photobioreactor cultivation. C16:0 and C20:5 are the most responsive fatty acids to temperature and light. A major proportion of EPA was found in phospholipids fraction. Both EPA and European standard biodiesel can be made by this process. Abstract: The marine eustigmatophyte Nannochloropsis is one of the potential producers of eicosapentaenoic acid (EPA), a valued nutraceutical. Nannochloropsis sp. was cultivated under photoautotrophic condition utilizing CO2 in a two phase cultivation process in order to enhance the eicosapentaenoic acid (EPA) productivity. It was cultivated in a photobioreactor up to late log phase for cell growth (phase I). Then, the culture was harvested and confronted to relatively low temperature (10 °C) and low light (30 μmol photons m −2  s −1 ) in both photobioreactor and Erlenmeyer flask (phase II), thus augmenting EPA% by 3.4 fold. Lower temperature with low light favored the synthesis of EPA although, biomass productivity, lipid content and lipid productivity were slightly decreased relative to phase I. The total lipids extracted from Nannochloropsis sp. fractionated into neutral lipids (NLs), glycolipids (GLs) and phospholipids (PLs) and a major proportion of EPA was found in phospholipids. Results suggested that low temperature and low light may ameliorate partitioning towards EPA in phospholipids.